Contextual compatibility of three empirically supported behavior therapies for cART adherence among patients with substance use disorders. Issue 1 (2nd January 2019) - Hartzler, Bryan; Dombrowski, Julia C.; Donovan, Dennis M.
ABSTRACT: Though substance use disorders complicate adherence to combination antiretroviral therapy (cART), cognitive–behavioral therapy (CBT), contingency management (CM), and motivational interviewing (MI) each demonstrate efficacy to improve cART adherence among substance-using patients. To inform dissemination of these therapies, this mixed-method study was undertaken involving a full-day site visit to each of four HIV care settings. At each setting, an initial administrator interview elicited setting data. Paired focus groups with setting staff and patients then served as forums for open discussion and live polling of the therapies' respective contextual compatibility. Focus group recordings were subjected to a phenomenological narrative analysis by multidisciplinary investigators, and staff/patient compatibility ratings were analyzed via generalized linear models. Findings include: (1) emergent themes among staff of adaptability, patient-centeredness, and mission-congruence as desired therapy attributes, (2) emergent themes among patients of intrinsic motivation, respect for patient autonomy in illness management, and fairness among service recipients as desired therapy attributes; and (3) comparatively stronger staff perception of compatibility for MI than CBT or CM, and a similar albeit less robust or reliable pattern among patients. Collective findings support MI as a behavior therapy of choice for broad dissemination to HIV care settings to improve cART adherence of patients with substance use disorders.